Surface enhanced Raman scattering specificity for detection and identification of dried bloodstains. (November 2021) - Reese, T.; Suarez, C.; Premasiri, W.R.; Shaine, M.L.; Ingraham, H.; Brodeur, A.N.; Ziegler, L.D.
Highlights: SERS spectra can be used to distinguish human and non-human dried bloodstains. SERS spectra of bloodstains are different than more than 30 red brown stains. Dried menstrual and peripheral blood can be distinguished by SERS. SERS spectra of blood exhibit do not show any interferences from backgrounds. A SERS based swab technique is demonstrated for bloodstain identification. Abstract: Surface enhanced Raman spectroscopy (SERS) provides highly specific vibrational signatures identifying dried blood for a variety of forensic applications. SERS spectra on Au nanoparticle substrates excited at 785 nm are found to identify dried stains of human and nonhuman blood from seven animals, and distinguish stains due to menstrual and peripheral blood. In addition, the unique SERS bloodstain spectrum is distinct from the SERS spectra of thirty red-brown stains of potential household substances that could be visually mistaken for bloodstains and from food stains that have been shown to give positive results with presumptive colorimetric blood tests. Finally, a SERS swab procedure has been developed and demonstrates that the substrates that a blood sample dried on does not offer any Raman or fluorescence interference for the SERS identification of dried blood. Such bloodstains on porous and nonporous materials are all identical and exclusively due to the heme moiety of hemoglobin. Optimized selection of the extraction solvent is found to control the chemical composition of molecular components appearing in the SERS spectrum of complex, multicomponent biological mixtures, such as body fluids. Graphical Abstract: ga1